The impact performance of headguards for combat sports - McIntosh, A. S.; Patton, D. A. (British Journal of Sports Medicine, 2015)
Background/aim: To assess the impact energy attenuation performance of a range of headguards for combat sports. Methods: Seven headguards worn during combat sport training or competition, including two Association Internationale de Boxe Amateur (AIBA)-approved boxing models, were tested using drop tests. An International Organization for Standardization (ISO) rigid headform was used with a 5.6 kg drop assembly mass. Tests were conducted against a flat rigid anvil both with and without a boxing glove section. The centre forehead and lateral headguard areas were tested. Peak headform acceleration was measured. Tests from a selection of drop heights and repeated tests on the same headguard were conducted. Results Headguard performance varied by test condition. For the 0.4 m rigid anvil tests, the best model headguard was the thickest producing an average peak headform acceleration over 5 tests of 48 g compared with 456 g for the worst model. The mean peak acceleration for the 0.4, 0.5 and 0.6 frontal and lateral rigid anvil impact tests was between 32% and 40% lower for the Top Ten boxing model compared with the Adidas boxing model. The headguard performance deterioration observed with repeat impact against the flat anvil was reduced for impacts against the glove section. The overall reduction in acceleration for the combination of glove and headguard in comparison to the headguard condition was in the range of 72-93% for 0.6 and 0.8 m drop tests. Conclusions The impact tests show the benefits of performance testing in identifying differences between headguard models.